Housing Trust Funds and Wisconsin: Funding for Lead Hazard Control - Zamastil, Kim; Sierzchula, William; Moran, Sean; Mauer, Jennie; Frank, Tora (My University, 2008)
The Wisconsin Department of Health and Family Services seeks funding for the rehabilitation of pre-1950 housing as a way to eliminate childhood lead poisoning in this state. The state constitution prohibits using Wisconsin funds for private building improvements. The authors? analysis examines one option to finance lead hazard control: housing trust funds. The report compares administering a statewide housing trust fund, enabling regional governments to develop their own funds, and working within the confines of the status quo.
For PA 869: Public Affairs Workshop, Domestic Issues